Exchange rates in target zones: Evidence from the Danish Krone - Stefan Reitz; Mark P. Taylor (Kiel Institute for the World Economy (IfW), 2013)
Although the ERM II rules allow the Danish krone to fluctuate against the euro within an official target zone of 4.5%, most of the time the exchange rate has remained in a narrow range around its unconditional mean. Estimating a Smooth Transition Autoregression Target Zone (STARTZ) model confirms that the exchange rate exhibits target zone dynamics consistent with a band of approximately 0.75 percent around its unconditional mean. We conclude that the Danmark Nationalbank intervention policy of intra-marginal operations successfully managed an informal target zone in the foreign exchange market.
Keywords: E58; F31; G15; 330; Target zone; STARTZ model; Intervention